Vitamin B2 content determination in liver paste by using acid and acid-enzyme hydrolysis - Basić Zorica; Kilibarda Vesna; Miletić Ivanka (Vojnosanitetski Pregled)
Background/Aim. Vitamin B2 is available in foodstuff in the form of coenzyme and in free form. For its content determination a few procedures should be performed (deliberation from a complex, extraction of free and deliberated form) and detection, identification and quantification. There is a particular problem in determination of vitamin B2 in the meat products. For a determination of total vitamin B2 content in liver paste two preparation procedures are compared: acid and acid-enzymatic hydrolysis. The aim of this study thus, was to compare the effectiveness of these two different procedures for vitamin B2 content determination in liver paste. Methods. High pressure liquid chromatography (HPLC) method with fluorescence detector, as specific and adequately sensitive for the foodstuff of a complex composition with a natural vitamin content, was used for determination of vitamin B2 in liver paste. Acid hydrolysis was performed with the application 0.1 M hydrochloric acid in a pressure cooker, and enzymatic hydrolysis was performed with the 10% takadiastase on 45 ºC within four hours. Ten samples of liver paste from the supply of the Serbian Army were examined. Separation was performed on the analytical column Nucleosil 50−5 C18 with mobile phase 450 ml CH3OH + 20 ml 5 mM CH3COONH4, and detection on the fluorescent detector with the variable wave length. Both methods were validated: examining a detection limit, quantification limit, specificity (because of a possible B2 vitamin interference with reagents), linearity of a peak area and standard concentration of B2 vitamin ratio in the range from 0.05 μg/ml to 2 μg/ml, precision for the 0.05 μg/ml concentration and recovery. Results. All the previously examined parameters validated both methods as specific, precise and reproductive, with a high recovery (98.5% for acid and 98.2% for acid - enzymatic hydrolysis), as well as linearity in a range that significantly superseded the expected content in the samples (r = 0.9994, and r = 0.99987). Hydrolysis procedures make a sample suitable for vitamin B2 determination. In the liver paste samples a high content of vitamin B2 was determined: 0.83 mg/100 g after acid hydrolysis, and 0.909 mg/100 g after acid-enzyme hydrolysis. There were statistically significantly higher values determined after the acid-enzyme hydrolysis (p < 0.05). Conclusion. Using acid-enzyme hydrolysis and separation instrument technique (liquid chromatography) with a fluorescent detector as detection system, statistically significantly greater vitamin B2 quantities were determined than after using acid hydrolysis procedure. Vitamin B2 content determined in ten liver paste samples was high (0.881 − 0.936 mg/100g) indicating that this meat product is a good vitamin B2 source.